The strategic role of women in economic growth through the lens of islamic economics in Indonesia - Umar, Umar; Dewi, Evi Retno Cristiyan; Jasnur, Avrilia; Arlinda, Mutiara (Privietlab, 2025)
This study aims to analyze the strategic role of women as pillars of economic growth within the framework of the Islamic economy in Indonesia. A mixed-method approach was employed that combined quantitative and qualitative techniques. The quantitative method utilized Structural Equation Modeling (SEM) to measure the influence of women's variables on economic growth. Meanwhile, the qualitative approach adopted a literature review to analyze the structure of the Islamic economic framework in Indonesia. The results indicate that the Gender Development Index (GDI) significantly mediates and strengthens the influence of women-related indicators on economic growth. Women's education emerged as the most dominant factor, both directly and indirectly, followed by women's income. Meanwhile, female labor force participation and professional engagement exerted significant indirect effects on the GDI. These findings underscore the importance of inclusive gender-based development policies to support Indonesia’s sustainable economic growth. Furthermore, the analysis reveals that women’s involvement in economic sectors—particularly in the halal industry, Islamic microfinance, and the management of Islamic social funds such as zakat and waqf—has a significant impact on equitable and sustainable economic development. The Islamic economy provides a holistic value framework for empowering women as economic actors and agents of social transformation who maintain a balance between spiritual values and material progress. This study recommends the formulation of gender-inclusive Islamic macroeconomic policies and the enhancement of Islamic financial literacy and access for women. Thus, women’s empowerment in the Islamic economy is not merely a matter of equality but a strategic foundation for achieving just and sustainable national economic growth